Contextual reflections on COVID-19 and informal workers in Nigeria (2020)
Purpose – The index case of COVID-19 in Nigeria was reported on 27 February 2020. Subsequently, the exponential increase in cases has brought about the partial and total lockdown of cities, the closure of all schools and the shutdown of government offices in order to curtail the spread of COVID-19. COVID-19 and its subsequent drastic curtailment policies have implications on vulnerable groups, especially, informal workers who constitute about 70% of the active working population in Nigeria. This reflective discourse critically engages the plight of informal workers in the context of the COVID-19 pandemic in Nigeria. Design/methodology/approach – The research was guided by the epistemology of pandemic interpretationism. It engages contextual reflections of the plight of economically vulnerable informal workers in Nigeria. Data were collected from secondary sources while rapid case studies were conducted with ten informal workers in Lagos and Ibadan. Afterwards, data were contextually analysed. Findings – Economically vulnerable informal workers in Nigeria have contextually interpreted COVID-19 as an elite disease, imported into Nigeria by the wealthy. In addition, the mass population views COVID-19 containment measures such as lockdowns, movement restrictions and stay-at-home orders as elitist policies, which are aimed at protecting the wealthy and frustrating the poor and economically vulnerable who live on the fringes of poverty. Many informal workers have slipped below the poverty line while struggling to supply livelihood needs, as they were unable to earn daily income and cannot access palliatives. Consequently, they are of the opinion that “Hunger Virus is deadlier than Corona Virus”. Originality/value – This paper is a contextual reflection on the plight of economically vulnerable informal workers during the COVID-19 pandemic lockdown and movement restrictions in Nigeria. It presents pandemic interpretationism as an epistemological guide and reflectively examines the poverty impact of COVID-19 on the Nigerian informal sector via contextual analyses of secondary data and rapid case studies. The paper uncovers various COVID-19 livelihood experiences and the responses of the informal workers; furthermore, it provides policy recommendations.